Determination of Salmonella in egg shell and egg content in some selected areas of Bangladesh (International Journal of Natural Sciences, 2016)
Salmonellosis is one of the most common and widely distributed food-borne diseases. It constitutes a major public health burden and represents a significant cost in many countries. Salmonella are known for its wide range host and can cause clinical diseases in some hosts while in others, can be asymptomatic. Poultry and eggs are considered as major sources for different pathogenic Salmonella serotypes. Eggs produced locally under the small scale layer farm may present a hazard to consumers which may increase the spread of Salmonella in the environment. To investigate the occurrence of Salmonella, a total of 72 samples were taken from 6 poultry farm in some selected areas of Bangladesh. Sampling program was executed between October and December, 2013 and samples were tested using standard laboratory methods. Data was collected through direct interview and structured questionnaire. Our study shows that, true prevalence of Salmonella in egg shell and egg contents were 0.093% and 0.068% respectively. The highest apparent prevalence in Udayan poultry farm (50%) and lowest in Liza poultry farm (16.67%). The average frequency of egg shell contamination is positively correlated with re-use of egg tray without disinfection. To the best of our knowledge, this is the first investigation on Salmonella spp. in selected local egg production farms in Chittagong. Further detail study is highly recommended.International Journal of Natural Sciences (2015), 5(2) 66-72